Respuesta :

Answer:

(1) (4x - 5y)(4x + 5y)

Step-by-step explanation:

Question 42

  • 16x² - 25y²
  • The identity to be used is : a² - b² = (a - b)(a + b)
  • (1) (4x - 5y)(4x + 5y)

Answer:

(1)  (4x - 5y)(4x + 5y)

Step-by-step explanation:

Difference of Two Squares:   [tex]a^2-b^2=(a-b)(a+b)[/tex]

Therefore, we can use The Difference of Two Squares to factor this expression quickly.

Given expression:  [tex]16x^2-25y^2[/tex]

[tex]16=4^2 \implies 16x^2=4x \cdot 4x=(4x)^2[/tex]

[tex]25=5^2 \implies 25y^2=5y \cdot 5y=(5y)^2[/tex]

Therefore:

[tex]16x^2-25y^2=(4x)^2-(5y)^2[/tex]

Using The Difference of Two Squares:

[tex](4x)^2-(5y)^2=(4x-5y)(4x+5y)[/tex]